2012
DOI: 10.1007/s00038-012-0406-5
|View full text |Cite
|
Sign up to set email alerts
|

No causal effect of unemployment on smoking? A German panel study

Abstract: Objectives This study analyses the effects of different unemployment durations on smoking behaviour in Germany by investigating smoking take-up, relapse, quitting and smoking intensity. Methods Longitudinal data from the German Socio-Economic Panel from the years 1998, 2001, 2002, 2004, 2006, and 2008 were used to examine the effect of unemployment (52,940 observations from 17,028 respondents, aged 17-65 years). Unemployment duration was measured at 1-6, 7-12, 13-24, and 24+ months. Effects were estimated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
(36 reference statements)
0
14
0
3
Order By: Relevance
“…7 in the appendix). Moreover, a comparison of smoking prevalence among unemployed and employed East Germans for the year 1998 reveals that the unemployed were not more likely to smoke than the employed (Robert Koch Institute 2000), and a German panel study covering the years 1998–2008 found no direct causal effect of unemployment on smoking (Schunck and Rogge 2012). This unclear relationship may be due to conflicting reactions to a weak employment market.…”
Section: Discussionmentioning
confidence: 99%
“…7 in the appendix). Moreover, a comparison of smoking prevalence among unemployed and employed East Germans for the year 1998 reveals that the unemployed were not more likely to smoke than the employed (Robert Koch Institute 2000), and a German panel study covering the years 1998–2008 found no direct causal effect of unemployment on smoking (Schunck and Rogge 2012). This unclear relationship may be due to conflicting reactions to a weak employment market.…”
Section: Discussionmentioning
confidence: 99%
“…New samples are added to the SOEP data at regular intervals to replenish the sample and ensure continuing representativeness of the population in Germany [ 29 , 30 ]. Since the SOEP covers a wide range of topics, including self-reported health behaviour—such as smoking beginning in 1998—it is widely used to study health related outcomes [ 32 , 33 , 34 , 35 ]. We used the SOEP data set version 29 which includes data until the year 2012.…”
Section: Methodsmentioning
confidence: 99%
“…However, no such association was found in research conducted in the US (Midanik et al 1995) or in the Netherlands (Henkens et al 2008). Being unemployed was found to be negatively associated with smoking cessation in a study among British adults (Giordano and Lindstrom 2011), but the transition from being employed to being unemployed was not shown to be associated with lower chances of smoking cessation in the samples of older British (Falba et al 2005) or German adults (Schunck and Rogge 2012). …”
Section: Introductionmentioning
confidence: 97%